Accidental Methadone Intoxication in Young Children: The Urgency of Early Diagnosis, Screening, and Safe Storage - Yusuf, Wan Nazirah Wan; Tang, Suk Peng; Ismail, Norzila; Low, Jen Hou; Rawi, Rowani Mohd (Journal of Chemical Health Risks, 2024)
Accidental methadone intoxication is increasingly recognized as a critical public health concern, particularly in households where opioid medications are accessible. We report accidental poisoning cases involving two young siblings, who presented with severe central nervous system depression, respiratory compromise, and cardiac depression. Initially they were treated as paracetamol intoxication based on information from their mother. Routine drug screening was negative for both patients. However, it was later confirmed as methadone poisoning. Fortunately following intensive therapy, both siblings recovered well without neurological sequelae. The delayed diagnosis underscores the challenges in detecting methadone poisoning with standard toxicology screens, highlighting the need for specialized testing methods not universally available. This case also emphasizes the critical importance of safe medication storage and heightened awareness among caregivers, healthcare providers, and the community regarding the risks associated with methadone exposure in children, especially in environments where opioid maintenance therapies like Methadone Maintenance Therapy (MMT) are prevalent.